(untitled) (The International Journal of Educational Sciences and Arts, 2024)
What I found in this research is that Socrates is the only one among the thinkers of antiquity who made self-knowledge the main goal of his teachings and the principle. The guide for all his activities proof famous of this saying know yourself (because when a person himself and know what is useful to him and distinguishes between what he can do and what he cannot do he supplies himself with what is necessary and lives happily and abstains from what is beyond his capabilities and avoids .the mistakes and misfortunes that arise from a person s ,knowledge of his inner world the feeling of a clear person of life that health of the mind the harmony of internal forces and external effectiveness and the satisfaction that is caused by moral behavior and results in the highest good and highest values. Socrates focus came on the relationship of identity this are associated whit freedom and responsibility because when a person knows himself and knows the responsibilities he has he controls his freedom for example a person bought a car and this is his freedom but his responsibility is to learn the rules of driving or another person expressed his opinion but his responsibility is to know the controls of speech that does not contain hatred hostility or violation of sharia and the law …etc therefore these responsibilities must be subjected to the controls of reason and with these issues the person becomes virtuous and he who acts according to them virtue only does good and whoever does good is happy according to this a virtuous society is achieved because virtue is knowledge and vice is ignorance